Social Media and Mass Communication in the Digital Era: A Narrative Review - Handayani, Widhia Seni; Junaidi (Indonesian Scientific Publication, 2024)
This narrative review examines the global impact of social media on mass communication practices, focusing on the shifts in communication formats, public participation, and the emerging challenges of misinformation and digital inequality. The study aimed to assess how digital platforms are transforming traditional mass communication and to identify systemic barriers limiting their effectiveness. A comprehensive literature search was conducted using Scopus, PubMed, and Google Scholar, applying inclusion criteria focused on peer-reviewed articles from the past decade addressing social media, mass communication, and digital transformation. The results reveal five critical themes: the evolution of communication style toward visual and participatory formats; the rise of citizen journalism enhancing local information access; the acceleration of misinformation and opinion polarization; the psychological impacts of digital engagement, particularly among youth; and the strategic adaptation of communication professionals in leveraging digital tools. Notably, disparities in infrastructure, policy, and digital literacy impede equitable access and utilization of social media across different regions. The findings underscore the need for inclusive media policies, digital literacy programs, and strategic investments in technological infrastructure. By addressing these systemic barriers, stakeholders can enhance the positive potential of social media in public discourse and health communication. This review contributes to a deeper understanding of digital communication dynamics and informs future policies and research targeting sustainable and equitable communication ecosystems.